Limited radiography - Campeau, Frances (Delmar/Cengage Learning, 2010)
A guide to limited radiographer training. It uses a simple to complex approach to teach a variety of multiskilled allied health professionals. It provides a fundamental imaging foundation and focuses on limited radiography as an occupation and important provider of patient care.